Birch bark tar and jewellery: The case study of a necklace from the Iron Age (Eckwersheim, NE France). (August 2018) - Courel, Blandine; Schaeffer, Philippe; Féliu, Clément; Thomas, Yohann; Adam, Pierre
Abstract: Organic residue analysis has been undertaken on an organic material found on a necklace with a pendant unearthed from a necropolis dated to the Early Iron Age (800–475 BCE) and located in Eckwersheim (NE France). The molecular composition of the substance, which was investigated using gas chromatography coupled to mass spectrometry, points towards an adhesive used to stick two bronze half-spheres to form a pendant. The predominance of triterpenoids from the lupane series led to the identification of the adhesive as a birch bark tar and constitutes a rare example of the use of such a material in jewellery in the past. Highlights: The study reports a rare archaeological example of birch bark tar used in jewellery. Birch bark tar was used as an adhesive to fashion a pendant (Iron Age, NE France). Conifer resin might have been added to the tar to improve the adhesive properties.